Penyuluhan Tentang Pergaulan Bebas Kepada Siswa-Siswi SMP Anak Soleh Desa Tambaksari Kabupaten Cilacap - Rahmiyani, Ira; Burhanudin, Aris; Athallah, Muhammad Dafa Naufal; Sabilla Nurrahmadewi; Nurcahyani, Gita Indah; Hutagalung, Juni; Arifin, Denadia Ramdiani; Nopiana, Gina Fitria (Journal of Smart Community Service, 2023)
Promiscuity is classified as behavior that can interfere with the welfare of others and harm both oneself and others. Common forms of adolescent indifference include drug use; free sex; Alcoholic beverages. Teenagers are unstable individuals whose emotions tend to get out of control through adolescent self-control. Other issues identified were reproductive health problems and risky behavior among adolescents. Adolescence is a period of learning, although teenagers have the opportunity to fulfill their potential but still need support, guidance and guidance from parents, educators and support to create a conducive environment. Several techniques were employed in this counseling activity, including presentations, discussions, question-and-answer sessions, pre-tests, and post-tests. 62 individuals participated in the counseling session. This counseling exercise aims to improve understanding and the ability of Anak Soleh Middle School students to put what has been taught into practice. Participants should find it simpler to learn from this activity thanks to the method selection that was used. In this extension activity, the usage of pre-test and post-test methodologies is employed as a success indication. The results of the pre-test and post-test show that students understand what is explained in the material of promiscuity, namely the meaning of promiscuity, the characteristics of promiscuity, the factors that cause promiscuity, the impact of promiscuity, and how to deal with promiscuity.